Traditional Fishing Gears, Fish Catch and Species Composition of Selected Floodplain Wetlands of Lower Gangetic Plains, West Bengal, India - Sandhya, K. M.; Roy, Aparna; Hassan, M. A.; Kumari, Suman; Mishal, P.; Lianthuamluaia, L.; Kumar, Vikash; Aftabuddin, M.; Bhattacharjya, B. K.; Meena, D. K.; Ali, Y.; Naskar, B. (Fishery Technology, 2019)
Floodplain wetlands (locally called as beels) are biologically sensitive habitats playing vital role in fish recruitment as well as acting as nursery ground for fishes and play an important role in the rural economy of West Bengal. Catch composition and details of fishing gears used in eight beels from four districts of West Bengal were documented. Gears based on their operation were categorised into active and passive fishing gears. Use of these gears were found to vary according to water depth, season, water area, type of fish species, availability of raw material for gear fabrication etc. The socio-economic background of the fishers as well as their traditional knowledge in fishing is also very important in the selection of gears. Most of the fishers were using gears made with netting material of nylon for catching the fishes. A total of 12 gear types along with their details, gear efficiency in terms of the type of species caught and the catch per day were recorded. Average fish catch/day was maximum for Berjal which varied from 75-105 kg comprising of stocked fishes like Indian Major Carps, Exotic carps as well as indigenous fishes. Use of small meshed nets was recorded in this region which may lead to imbalances in fish stocks affecting icthyodiversity as well as sustainable exploitation of fishes. Creating awareness among the beel fishers on the adverse effects of fine mesh nets on biodiversity was felt necessary.